Rationale for Stereotactic Body Radiation Therapy in Treating Patients with Oligometastatic Hormone-Naïve Prostate Cancer - Bhattasali, Onita; Chen, Leonard; Tong, Michael; Lei, Siyuan; Collins, Brian T.; Krishnan, Pranay; Kalhorn, Christopher; Lynch, John; Suy, Simeng; Dritschilo, Anatoly; Dawson, Nancy; Collins, Sean (Frontiers in Oncology, 2013)
Despite advances in treatment for metastatic prostate cancer, patients eventually progress to castrate-resistant disease and ultimately succumb to their cancer. Androgen deprivation therapy (ADT) is the standard treatment for metastatic prostate cancer and has been shown to improve median time to progression and median survival time. Research suggests that castrate-resistant clones may be present early in the disease process prior to the initiation of ADT. These clones are not susceptible to ADT and may even flourish when androgen-responsive clones are depleted. Stereotactic body radiation therapy (SBRT) is a safe and efficacious method of treating clinically localized prostate cancer and metastases. In patients with a limited number of metastatic sites, SBRT may have a role in eliminating castrate-resistant clones and possibly delaying progression to castrate-resistant disease.